PERAN PENDIDIKAN KEWIRAUSAHAAN DALAM MENINGKATKAN KOMPETENSI MAHASISWA ADMINISTRASI PERKANTORAN DI UNIVERSITAS NEGERI MAKASSAR - Nasir (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2025)
This study aims to identify the role of entrepreneurship education in improving the competence of students of the Office Administration Education Study Program, State University of Makassar. The method used in this study is a qualitative approach with interview and observation techniques as a data collection tool. The research participants consisted of students, lecturers in entrepreneurship courses, and alumni who have entered the business world. The main findings of this study show that entrepreneurship education contributes significantly to developing managerial skills, creativity, and independent and innovative attitudes in students. In addition, project-based learning and hands-on practice in the business world have a positive impact on students' readiness to start a business or enter the world of work. In conclusion, entrepreneurship education in the Office Administration Education Study Program, State University of Makassar can improve student competence, especially in terms of practical skills and entrepreneurial attitudes necessary to succeed in the professional world. Therefore, entrepreneurship education needs to continue to be strengthened and adjusted to the needs of the job market and industry.